Development of national health data warehouse frame work for Bangladesh - Khan, Shahidul Islam (IIUC Studies, 2022)
Data Warehouse (DW) integrates data from two or more sources into a repository for reporting, analysis, and knowledge discovery. This technology can be used in healthcare to develop National Health Data Warehouse (NHDW) that combines patient information from clinics, hospitals, laboratories, diagnostic centers, etc. In this research, we propose a framework for NHDW based on studying different global frameworks and conducting surveys among the potential stakeholders of the framework. Here, patient data will be collected in two phases: physical data collection and data collection over the internet. We did surveys on different healthcare organizations among patients, medical staff, and doctors. The survey questionnaire was divided into four sections: personal information, information privacy and security, performance, and usability to know the requirement of the stakeholders. As healthcare data is very sensitive and can be misused, providing privacy for these patients' information is properly addressed in this framework. The NHDW framework may significantly improve our healthcare services in Bangladesh. IIUC Studies Vol.19, December 2022: 53-68